Differential responses of arbuscular mycorrhizal fungi to nitrogen addition in a near pristine Tibetan alpine meadow. Issue 3 (19th June 2014) - Zheng, Yong; Kim, Yong‐Chan; Tian, Xiao‐Fang; Chen, Liang; Yang, Wei; Gao, Cheng; Song, Ming‐Hua; Xu, Xing‐Liang; Guo, Liang‐Dong
Abstract Elucidating the responses of soil microbial abundance and community composition to nitrogen (N) addition is important for predicting ecosystem function under increased atmospheric N deposition. We examined the arbuscular mycorrhizal (AM) fungal community under three N forms (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh13028dt0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NH4+</alternatives>‐N, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh13028dvj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives>‐N, and NH4NO3‐N) and two N rates (1.5 and 7.5 g N m−2 year−1) in an alpine meadow of the Qinghai–Tibetan Plateau. AM fungal extraradical hyphal density was significantly decreased by <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh13028dfx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NH4+</alternatives>‐N in May, but was not affected by N form nor N rate in August. N rate, but not N form, significantly affected AM fungal spore density; high N rate decreased spore density. No direct N addition effect was observed on AM fungal community; however, soil available phosphorus, pH, and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh13028dgg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives>‐N were considered as important factors that influenced AM fungal community composition. Structural equation model results showed that N rate, not N form, strongly affected soil characteristics, which directly influenced community compositions of plants and AM fungi, as well as spore density. Therefore, AM fungal community was influenced by N addition, primarily because of altered soil characteristics, and partially by a modified plant community, but not or just slightly by direct N addition effects in this alpine meadow ecosystem.